Should personal practice be part of cognitive behaviour therapy training? Results from two self‐practice/self‐reflection cohort control pilot studies. (20th August 2020) - Scott, Jane; Yap, Keong; Bunch, Katie; Haarhoff, Beverly; Perry, Helen; Bennett‐Levy, James
Abstract : There are good theoretical and empirical grounds to suggest that personal practices (PPs; e.g., self‐practice/self‐reflection [SP/SR] programmes, meditation programmes and personal therapy) can have a positive impact on therapist skills and client outcomes. However, to date, a weakness in many PP studies is the lack of cohort control groups. The two pilot studies reported in this paper examined SP/SR programmes integrated into postgraduate psychology training and are the first to include cohort control groups. Study 1 compared outcomes of students assigned to either SP/SR ( n = 17) or a cognitive behaviour therapy (CBT) book study group ( n = 13) during their first clinical placement. Study 2 compared outcomes of students who completed the SP/SR programme as part of CBT training ( n = 12) with participants who completed the same CBT training in the previous year without an SP/SR programme ( n = 17). Significant improvements in therapist confidence for the SP/SR groups were found in both studies. Study 2 also showed significantly higher therapist self‐awareness and lower burnout scores in the SP/SR group. These studies are limited by their small sample size and the lack of random allocation. Nevertheless, they provide preliminary empirical evidence demonstrating large effects of PP on trainees' personal and therapist selves and offer a basis for further research using randomized controlled designs with larger sample sizes.